Examining the success of Malian music as world music - Hickson, Jim (International Library of African Music, 2022)
Malian music is ubiquitous in world music. Indeed, Malian artists consistently appear more often and rank higher in world music record charts than artists of any other nationality. While the concept and industry of world music and the histories and workings of Malian music have been examined at length in the past, scholarship on the intersection of the two has been sparse. This article investigates how various marketing techniques and narrative tropes have been used to secure Mali’s on-going presence within world music. Tuareg essouf band Tinariwen is introduced as a specific case study to allow exploration into themes of audience familiarity and unfamiliarity; the use of wider narratives to promote music; and the role of cultural brokers in this process. Malian music can be considered ideal for the world music markets, with musical, narrative and political forces aligning in an optimal manner to facilitate the most effective strategies of marketing towards world music audiences. By studying the dominance of Malian music in world music, we can examine more clearly the mechanics of the industry, but also the attitudes and behaviours of the world music audience and the artistic, industrial and even institutional practices and processes that define world music as a whole.
Keywords: Tuaregs; Audiences; World music; Marketing; Music; Mali; Music Industry; African Music